Strategies to Enhance the Productivity of Yellow Bean Coffee Through Seed Certification and Value-Added Nursery Practices - Hermina, Tinneke; Alkautsar, Muslim; Romdhon, Mochamad; Fauziah, Hanifah; Basit, Acep Abdul (Yayasan Sinergi Kawula Muda, 2026)
This study aims to develop strategic approaches to enhance the productivity of Yellow Caturra coffee cultivated in Mount Mandalagiri, Garut Regency, Indonesia. Since 2012, Mandalagiri coffee farmers have experienced a decline in yields, primarily due to the use of seedlings that are not well-suited to the volcanic soil conditions of the region. Although the area possesses significant potential for coffee cultivation expansion through the national social forestry programme, the availability of certified Yellow Caturra seedlings remains limited. This research employed a qualitative descriptive approach to obtain an in-depth understanding of the certification process for Yellow Caturra nurseries and the potential value added from nursery activities to improve productivity. Data were analysed using the SOAR framework (Strengths, Opportunities, Aspirations, and Results) to identify strategic priorities for sustainable productivity enhancement. The findings highlight three main strategies: (1) the selection of superior Yellow Caturra parent plants and the integration of Good Agricultural Practices (GAP) within nursery operations to ensure seed certification; (2) capacity building and skill enhancement for seed breeders to strengthen the quality and scalability of seedling production; and (3) the promotion of Yellow Caturra coffee as Garut’s distinctive specialty product. These strategies underline the critical roles of certification, human resource development, and regional branding in improving productivity and ensuring the long-term sustainability of coffee cultivation in Mandalagiri.